The Germans and the Holocaust : popular responses to the persecution and murder of the Jews - Schrafstetter, Susanna; Steinweis, Alan E. (New York ; Oxford : Berghahn Books, 2015)
For decades, historians have debated how and to what extent the Holocaust penetrated the German national consciousness between 1933 and 1945. How much did "ordinary" Germans know about the subjugation and mass murder of the Jews, when did they know it, and how did they respond collectively and as individuals? This compact volume brings together six historical investigations into the subject from leading scholars employing newly accessible and previously underexploited evidence. Ranging from the roots of popular anti-Semitism to the complex motivations of Germans who hid Jews, these studies illuminate some of the most difficult questions in Holocaust historiography, supplemented with an array of fascinating primary source materials.
Appendix F -- SD Reports on German Popular Opinion during World War II (Excerpts) 1943-44 -- Appendix G -- Statement by Benno Schülein (Excerpt) 1946 -- Appendix H -- Statement by Dr Sophie Mayer (Excerpts) 1946 -- Appendix I -- Moses Moskowitz, ""The Germans and the Jews: Postwar Report"" (Excerpts) 1946 -- Index.
"The contributions to this volume are based on lectures delivered at a symposium on The German People and the Persecution of the Jews, which took place at the University of Vermont on April 22, 2012"--Preface
Includes index.
Print version record.
Includes bibliographical references and index.
JSTOR
Keywords: Jews -- Persecutions -- Germany -- History -- Congresses; Antisemitism -- Germany -- History -- 19th century -- Congresses; Antisemitism -- Germany -- History -- 20th century -- Congresses; Jews -- Germany -- Public opinion -- Congresses; Public opinion -- Germany -- Congresses; Germany -- Ethnic relations -- History -- Congresses; Juifs -- Persécutions -- Allemagne -- Histoire -- Congrès.; Antisémitisme -- Allemagne -- Histoire -- 19e siècle -- Congrès.; Antisémitisme -- Allemagne -- Histoire -- 20e siècle -- Congrès.; Juifs -- Allemagne -- Opinion publique -- Congrès.; Opinion publique -- Allemagne -- Congrès.; HISTORY -- Europe -- Western; HISTORY / Holocaust; Antisemitism; Ethnic relations; Jews -- Persecutions; Jews -- Public opinion; Public opinion; Germany; Antisemitismus; Judenvernichtung; Öffentlichkeit; Deutschland; 1800-1999; Conference papers and proceedings; History; Konferenzschrift -- 2012 -- Burlington, Vt